PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA, DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN NON MEDIS RUMAH SAKIT ISLAM MALANG - Isvandiari, Any; Purwanto, Anang (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2017)
The research was purposed to find out whether there was any partial or simultaneous effects of organizational culture, work discipline, and job satisfaction toward the work performance of non-medical employees at Malang Islamic Hospital. The population of this research is 93 non-medical employees and 62 are selected as sample. Sampling technique used is purposive sampling of non-medical employees which already a permanent employees. Data analysis was made with multiple regression analysis. Analysis result show that organizational culture, work discipline, and job satisfaction have any partial and simultaneous effects toward the performance of non-medical employees at Malang Islamic Hospital.